2000
DOI: 10.1002/chp.1340200306
|View full text |Cite
|
Sign up to set email alerts
|

On-site to on-line: Barriers to the use of computers for continuing education

Abstract: Program planners may wish to offer training in new technologies during on-site conferences, provide CD-ROMs as take-home instructional materials, or promote technology awareness in other ways to help clinicians prepare for changes in the electronic delivery of health care and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 6 publications
0
56
0
Order By: Relevance
“…In contrast, researchers in medicine 15 and nursing 6,24 showed that both a lack of self-confidence and time away from family were often reported as major barriers. The uniqueness of these professions may explain the different perceptions regarding these barriers to formal CE; each profession requires unique knowledge and skills.…”
Section: Barriers To Athletic Training Ce Activitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, researchers in medicine 15 and nursing 6,24 showed that both a lack of self-confidence and time away from family were often reported as major barriers. The uniqueness of these professions may explain the different perceptions regarding these barriers to formal CE; each profession requires unique knowledge and skills.…”
Section: Barriers To Athletic Training Ce Activitiesmentioning
confidence: 98%
“…We should also recognize that other informal CE activities, such as professional networking and reading professional journals, can be preferred by ATs and other health professionals. 4,7,[12][13][14][15][16][17][18] These informal CE activities are completed and valued because they are more holistic and individualized to meet a practitioner's learning needs than is formal CE. 6 In addition to CE preferences, the barriers that prevent practitioners from participating in CE also must be appreciated.…”
mentioning
confidence: 99%
“…Online and other interactive multimedia CE activities are growing in popularity in other health care fields as well. [21][22][23][24][25][26][27][28] The flexibility of online CE activities is ideal for ATs, who can complete them according to their specific learning needs whenever, wherever, and however they choose.…”
Section: Participation In Formal Ce Activitiesmentioning
confidence: 99%
“…Another Australian study shows that the local general practitioners' main barriers to CME were lack of time and loss of income [18]. Mamary and Charles, on the other hand, have investigated barriers to the use of computers for continuing education [19]. Their study results show that the most frequently reported reason for not using the computer for continuous education was a lack of computer skills and a lack of knowledge about how to use the Internet.…”
Section: Introductionmentioning
confidence: 99%